2022
DOI: 10.1096/fj.202200313rr
|View full text |Cite
|
Sign up to set email alerts
|

The SLC26A9 inhibitor S9‐A13 provides no evidence for a role of SLC26A9 in airway chloride secretion but suggests a contribution to regulation of ASL pH and gastric proton secretion

Abstract: The solute carrier 26 family member A9 (SLC26A9) is an epithelial anion transporter that is assumed to contribute to airway chloride secretion and surface hydration. Whether SLC26A9 or CFTR is responsible for airway Cl − transport under basal conditions is still unclear, due to the lack of a specific inhibitor for SLC26A9. In the present study, we report a novel potent and specific inhibitor for SLC26A9, identified by screening of a drug-like molecule library and subsequent chemical modifications. The most pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…They concluded that SLC26A9 is the primary source of constitutive anion secretion across HBE [ 18 ]. We could not reproduce their results in our recent study using CFTR inhibitors and the novel SLC26A9-inhibitor S9-A13 [ 21 ]. S9-A13 potently inhibits whole cell currents and iodide quenching in SLC26A9-overexpressing cells, but does not inhibit CFTR.…”
Section: Basal Airway Cl- Secretion By Cftrmentioning
confidence: 83%
See 4 more Smart Citations
“…They concluded that SLC26A9 is the primary source of constitutive anion secretion across HBE [ 18 ]. We could not reproduce their results in our recent study using CFTR inhibitors and the novel SLC26A9-inhibitor S9-A13 [ 21 ]. S9-A13 potently inhibits whole cell currents and iodide quenching in SLC26A9-overexpressing cells, but does not inhibit CFTR.…”
Section: Basal Airway Cl- Secretion By Cftrmentioning
confidence: 83%
“…That’s because GlyH101 is a potent inhibitor of CFTR, and also shows off-target effects by inhibiting Ca 2+ channels [ 19 , 20 ]. As outlined below, there is now good evidence that CFTR, but not SLC26A9 generates a basal airway Cl- conductance even in the absence of any stimuli [ 21 ].…”
Section: Expression Of Slc26a9 In the Lung And Its Potential Role For...mentioning
confidence: 99%
See 3 more Smart Citations